The rhetorical devices for marketing and branding Johannesburg as a city: a critical review - Sihlongonyane, Mfaniseni Fana (Sage Publications, 2015)
Since the founding of the city of Johannesburg in 1886, the city has taken up the quest to project a modernist image whose meaning has an international reach and a local foundation. In this endeavor, its locational advantages, product (gold), ethnicity (African), race, and class (notwithstanding the interconnections of these factors) has been used as part of the branding narratives of the city. However, the use of these factors has been closely shaped by the political ideologies of the day. While the brand imaginary of the apartheid government was largely Euro-modernist and dependent on the use of locational, product, and racial influences, the post-apartheid vision has been Afro- modern relying on the fusion of global and African images informed by ethnicity and class. Whereas the two governments had political systems that differ widely on ideological grounds, both have had to contend with the indelible influence of the global market in the production of the city’s brand narratives. The paper traces the different trajectories of image/branding narratives of the city from its founding to the present. Consequently, it posits the theoretical argument that a global-African imaginary as a form of African modernity is the driving force for the branding of Johannesburg. The goal of the paper is not to assess the effectiveness of the marketing campaigns but to gain insights into the city’s self-reflective efforts at re-imagining the city’s identity as captured in branding texts through a critical and interpretive approach. The paper presents an Afro-modernity that is relational and inclusively intercultural but perverted by the hegemonic impact of neoliberal policy and its adverse articulations of globalization.
Cities are no longer just built, they are imagined
Keywords: City branding; Global imaginary. African.; Global Africanization.; African modernity; Branding. South Africa, Johannesburg